1992
DOI: 10.2116/analsci.8.553
|View full text |Cite
|
Sign up to set email alerts
|

Calibration-Free Measurement of Sodium and Potassium in Undiluted Human Serum with an Electrically Symmetric Measuring System

Abstract: The limitations of ion-selective electrodes (ISEs) presently in use mainly concern the stability of the calibration values. By applying optimal membrane technologies and optimized reference electrodes a perfectly symmetric measuring system including a symmetric ISE membrane has been developed. Thus, stable standard potentials of the cell assembly, both before and after serum contact, as well as theoretical slopes of the electrode response have been obtained. Results of calibration-free assays of K+ and Na+ con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…When a0 .1m KCl solution is used as both the sample and reference electrolyte,asymmetrical potentiometric cell is formed, and the theoretical emf value is 0mV. [18] As Figure 4a shows,the measured emf value is 0.3 AE 2.1 mV (number of samples, n = 3), correlating well with the predicted value.A lthough the HHCAE membrane exhibits limited selectivity towards various hydrophilic anions,i ti s chosen specifically for clinical Cl À sensing (98-107 mm in blood serum) because its use decreases interference from lipophilic ions (such as Br À or SCN À ) [19] and biofouling caused by lipids, [14] and also resists Donnan failure at high ion concentrations because of its high ion-exchange capacity. [20] As the HHCAE membrane was obtained with Br À as counterions,C l À substitution was required before device fabrication to ensure an accurate response (see Figure S2).…”
supporting
confidence: 53%
“…When a0 .1m KCl solution is used as both the sample and reference electrolyte,asymmetrical potentiometric cell is formed, and the theoretical emf value is 0mV. [18] As Figure 4a shows,the measured emf value is 0.3 AE 2.1 mV (number of samples, n = 3), correlating well with the predicted value.A lthough the HHCAE membrane exhibits limited selectivity towards various hydrophilic anions,i ti s chosen specifically for clinical Cl À sensing (98-107 mm in blood serum) because its use decreases interference from lipophilic ions (such as Br À or SCN À ) [19] and biofouling caused by lipids, [14] and also resists Donnan failure at high ion concentrations because of its high ion-exchange capacity. [20] As the HHCAE membrane was obtained with Br À as counterions,C l À substitution was required before device fabrication to ensure an accurate response (see Figure S2).…”
supporting
confidence: 53%
“…The isotopes at m/z 24 and 25, originating in part from magnesium in the serum, are just visible. The isotope appearing at m/z 30 is most likely due to a mixture of 15 N 2 1 , 14 N 15 NH, 14 NO 1 and 30 Si ions. A separate study on an unspiked serum showed no evidence of C 2 1 or CN 1 interferences on the magnesium isotopes.…”
Section: Methods Designmentioning
confidence: 99%
“…[2][3][4] For example, Fuchs et al 2 compared the performance of a glass membrane ISE system with flame photometry obtaining a correlation coefficient better than 0.98. Numerous other studies have been reported using ISE systems, [5][6][7][8][9][10][11][12][13][14][15][16][17][18] which generally fall into two categories, one involving a direct method where no dilution of the sample takes place and an indirect method where the sample is mixed with a diluent prior to the measurement. ISE measurements are subject to several errors.…”
Section: Introductionmentioning
confidence: 99%
“…Symmetrical measuring cell for the sensing of potassium and sodium ions in undiluted serum without prior calibration. 6 Two reference electrodes with free-flowing liquid junctions were used in this arrangement. While this approach was not maintenance-free, a residual error of just a fraction of a millivolt was found.…”
Section: ■ Using Robust Methodologies: From Amperometry To Coulometrymentioning
confidence: 99%
“…An early study by Rumpf et al demonstrated the absolute measurement of potassium and sodium levels in serum by ion-selective electrodes using a highly symmetrical measurement cell; see Figure . The authors did not achieve a maintenance-free measurement, since high flow rates of the reference electrolyte and intermittent cleaning steps were required to renew the two reference electrodes and the side of the sensing membrane exposed to the biological fluids.…”
Section: A Challenging Case Study: Clinical Diagnostics Of Blood Elec...mentioning
confidence: 99%